The use of the steam approach in teaching management disciplines (MMIT Proceedings, 2025)
The article discusses the possibilities of applying the STEAM approach in the process of teaching management disciplines in order to form students' practice-oriented management competencies. Specific examples of using the STEAM approach in teaching management, human resources management, and marketing are presented.